Systematic Review: Efek Nanoplastik terhadap Metilasi DNA pada Manusia - Anggit Wirama Siwidati; Abdul Rohim Tualeka (Universitas Airlangga, 2023)
Background: Along with the times, plastic pollution is increasing and this is a problem throughout the world, especially in developing countries due to its very large amount, persistent nature and widespread use. Objectives: The purpose of this systematic review is to determine the effect of nanoplastics on deoxyribonucleic acid (DNA) methylation in humans Methods: The method used is PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses). Data search in the form of articles or journals is carried out using the keywords